2013
DOI: 10.1002/chin.201336203
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Microwave Synthesis as a Part of Green Chemistry for the Synthesis of Novel 1,2,4‐Triazole Derivatives

Abstract: Microwave Synthesis as a Part of Green Chemistry for the Synthesis of Novel 1,2,4-Triazole Derivatives -[79 refs.]. -(CHAWLA, A.; KAUR, P.; Int. Res. J. Pharm. 4 (2013) 1, 49-72, http://dx.doi.org/10.7897/2230-8407.04309 ; CT Inst. Pharm. Sci., Jalandhar 144 008, Punjab, India; Eng.) -Lindner 36-203

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Therefore, the discovery and development of new effective and selective anticancer drugs are of high importance in modern cancer researches. 1,2,4-Triazole derivatives have their chance with these researches with a good results [41,59] [70].…”
Section: Anticancer and Antitumor Activitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the discovery and development of new effective and selective anticancer drugs are of high importance in modern cancer researches. 1,2,4-Triazole derivatives have their chance with these researches with a good results [41,59] [70].…”
Section: Anticancer and Antitumor Activitiesmentioning
confidence: 94%
“…Triazoles have two tautomeric forms: 1H-1, 2, 4triazole (3) and 4H-1,2,4-triazole (4)[41]. Many studies have been indicated that is tautomer (3) more sTable than tautomer (4)[42].…”
mentioning
confidence: 99%
“…1, 2, 4-Triazoles have two tautomeric forms: 1H-1, 2, 4 triazole (3) and 4H-1,2,4-triazole (4) [24]. Many studies have shown that tautomer (3) is more stable than tautomer (4).…”
Section: Tautomerism In 124-triazolesmentioning
confidence: 99%